Environmental fragmentation tendency: the Sprawl Index - Bernardino Romano (European Regional Science Association (ERSA), 2004)
About the matter of the environmental fragmentation due to settlement structure, an important issue is the “fragmentation tendency”. This phenomenon is linked to territorial sprawl sensibility and is determined by different land and urban characteristics. If the general ecological conditions are good, we can be sure that every animal species will increase their individuals number and will occupy larger areas and places. So we can say that this phenomenon is the same for human component, when the morphological, economic, climatic and social conditions are favorable. This means that we could draw the probable evolution of the settlement pattern in the future in order to particular aspects of the territory, as the altitude, slope, land use, exposure, infrastructures and urban location. We can also obtain the particular index (sprawl index) from the cited parameters, to measure the territorial sensibility toward the urban sprawl phenomena and individuate which areas are more critical than others in terms of future environmental fragmentation. Is very interesting to compare the results of these elaborations with the contents of the local planning instruments, to verify if the plan follows and favours these “human ecological” tendencies. The elaboration of the SIX (Sprawl Index) that we present in this paper has been developed and experimented on the study case of Umbria Region (Italy) in the context of the studies finalized at the RERU (Umbria Region Ecological Network).
Keywords: 330